2022
DOI: 10.1038/s41598-022-19371-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of luseogliflozin and voglibose on high-risk lipid profiles and inflammatory markers in diabetes patients with heart failure

Abstract: Sodium-glucose cotransporter 2 inhibitors could reduce cardiovascular events in patients with heart failure irrespective of diabetes status. In this prespecified sub-analysis of randomised-controlled trial, we investigated the efficacy of luseogliflozin (2.5 mg daily), a sodium–glucose cotransporter 2 inhibitor, with that of voglibose (0.6 mg daily), an alpha-glucosidase inhibitor, on high-risk lipid profile and inflammatory markers in patients with type-2 diabetes and heart failure. Among the 157 patients stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Of the 34 trials from which data were used for this analysis, most of the studies were of a parallel design, except for two crossover designs. Except for three multinational trials (Garvey et al, 2018;Oldgren et al, 2021;Docherty et al, 2022), most trials were recruited from ten different countries: 17 from Japan (Kaku et al, 2014;Kashiwagi et al, 2015a;Kashiwagi et al, 2015b;Kashiwagi et al, 2015c;Ishihara et al, 2016;Ito et al, 2017;Shigiyama et al, 2017;Hattori, 2018;Sato et al, 2018;Seino et al, 2018;Aso et al, 2019;Koshizaka et al, 2019;Katakami et al, 2020;Kinoshita et al, 2020;Sakurai et al, 2020;Ejiri et al, 2022;Takahashi et al, 2022); three from Germany (Bosch et al, 2019;Kahl et al, 2020;Thiele et al, 2021); two from Denmark (Eickhoff et al, 2020;Omar et al, 2022); two from the United Kingdom (Bailey et al, 2012;Brown et al, 2020); two from Thailand (Phrommintikul et al, 2019;Phrueksotsai et al, 2021); one from China (Hao et al, 2022); one from Austria (Antlanger et al, 2022); one from Brazil (Sposito et al, 2021); one from Finland (Latva-Rasku et al, 2019); and one from the Netherlands (Dekkers et al, 2018)). The study characteristics are listed in Table 1.…”
Section: Search Results and Description Of The Included Studiesmentioning
confidence: 99%
“…Of the 34 trials from which data were used for this analysis, most of the studies were of a parallel design, except for two crossover designs. Except for three multinational trials (Garvey et al, 2018;Oldgren et al, 2021;Docherty et al, 2022), most trials were recruited from ten different countries: 17 from Japan (Kaku et al, 2014;Kashiwagi et al, 2015a;Kashiwagi et al, 2015b;Kashiwagi et al, 2015c;Ishihara et al, 2016;Ito et al, 2017;Shigiyama et al, 2017;Hattori, 2018;Sato et al, 2018;Seino et al, 2018;Aso et al, 2019;Koshizaka et al, 2019;Katakami et al, 2020;Kinoshita et al, 2020;Sakurai et al, 2020;Ejiri et al, 2022;Takahashi et al, 2022); three from Germany (Bosch et al, 2019;Kahl et al, 2020;Thiele et al, 2021); two from Denmark (Eickhoff et al, 2020;Omar et al, 2022); two from the United Kingdom (Bailey et al, 2012;Brown et al, 2020); two from Thailand (Phrommintikul et al, 2019;Phrueksotsai et al, 2021); one from China (Hao et al, 2022); one from Austria (Antlanger et al, 2022); one from Brazil (Sposito et al, 2021); one from Finland (Latva-Rasku et al, 2019); and one from the Netherlands (Dekkers et al, 2018)). The study characteristics are listed in Table 1.…”
Section: Search Results and Description Of The Included Studiesmentioning
confidence: 99%
“…No significant changes were observed in LDL-C and ApoB levels. In a study by Ejiri et al [ 34 ] using luseogliflozin in patients with diabetes and heart failure with baseline lipid profiles at normal range, no significant changes were observed in small dense LDL-C, TG, or LDL-C levels. In a retrospective analysis by Kubota et al [ 35 ], 63 patients with T2DM on usual doses of SGLT2-i (Empagliflozin, Canagliflozin, Dapagliflozin, or Tofogliflozin), showed a significant decrease in total cholesterol and non-HDL-C levels, but no changes in TG, HDL, or LDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
“…Gürkan et al reported that 6 months of dapagliflozin therapy decreased the serum levels of LDL-cholesterol and TGs in T2DM patients [ 76 ]. Moreover, in another clinical study, 6 months of SGLT2i therapy with luseogliflozin decreased the LDL-cholesterol and increased the HDL-cholesterol levels in T2DM patients [ 77 ].…”
Section: Sglt2 Inhibitors and Lipid Metabolismmentioning
confidence: 99%
“…Bosch et al performed a clinical trial on patients with T2DM and found that empagliflozin had no significant effect on the total cholesterol, HDL-cholesterol, and LDL-cholesterol levels [ 82 ]. Another more recent study also showed that treatment with luseogliflozin and voglibose had no significant effect on the cholesterol profile in T2DM patients [ 77 ]. It showed that luseogliflozin had no significant effect on malondialdehyde, LDL particles, and small dense LDL particle cholesterol [ 77 ].…”
Section: Sglt2 Inhibitors and Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation